Reinventing the Self in Bharati Mukherjee’s Jasmine - Sharma, Radha Devi (Crossing the Border: International Journal of Interdisciplinary Studies, 2017)
Bharati Mukherjee’s Jasmine is a story of a young Punjabi woman named Jasmine whose life takes her from India to the United States, where she goes through many different destinies with her effort to reinvent her coherent self. Searching for and defining a new identity is a central question for immigrants living in a foreign land. The confusion of identity and cultural conflict pushes the immigrants into an identity crisis. The novel exposes how Jasmine, the female protagonist, as an outsider, strives to shape her identity to fit in the mainstream American society. Fortunately, she encounters confirmations of her shifting identity in different stages of her life. Instead of rejecting these identities and names in various phases, she seeks to create a harmonious relationship with those identities. In this context, this paper tries to explore on how she struggles throughout her life to reinvent the coherent self by her constant effort to assimilate to the alien culture and setting. Crossing the Border: International Journal of Interdisciplinary Studies Vol.4(1) 2016: 29-38